Cyber crimes with cryptocurrencies: analysis of brazilian legislation and case studies - Granado Filho, Flavio; Sozzo, Bruna (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 40 No especial (2024): Computação, 2024)
The rising popularity of cryptocurrencies has been met with an alarming surge in cybercrimes, with money laundering emerging as a primary concern. The intrinsic characteristics of cryptocurrencies, such as decentralization and potential anonymity, make them an attractive vehicle for illicit activities. Given the severity of this situation, it is vital to be well-informed about the security strategies that can be employed to counteract it. In this article, we delve deeply into the subject, conducting a meticulous analysis of case studies, reviewing contemporary literature, and scrutinizing Brazilian legislation concerning cybercrimes associated with cryptocurrencies. Our goal is to shed light on the primary criminal methods and, most importantly, provide robust guidelines for their prevention.